2005
DOI: 10.1177/1094670504271153
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Approach for Allocating Service Recovery Efforts to Reduce Internal Failures

Abstract: Prior research substantiates the value of compensating customers for poor quality. However, little guidance has been provided for the recovery of errors while service delivery is in progress. The authors provide analytical models inspired by reliability theory to guide managers in allocating their investments in service recovery. Models are constructed to achieve four different objectives and converted to Lagrangian formulations for solution. Example solutions illustrate the contrast in investment allocations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…To prevent further damage, service companies attempt to recover the situation by offering the customer some form of compensation for the loss incurred (Patterson, Cowley, and Prasongsukarn 2006). Complaint recovery refers to the steps companies take to neutralize the potentially drastic effects of the failure and restore the customer to a state of satisfaction (Patterson, Cowley, and Prasongsukarn 2006; Simons and Kraus 2005). A recent comprehensive review of journal articles on complaint recovery suggests nearly 97% of the published articles tested the effectiveness of recovery responses while revealing a total of 21 different potential recovery measures (Van Vaerenbergh et al 2019).…”
Section: Conceptual Framework and Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent further damage, service companies attempt to recover the situation by offering the customer some form of compensation for the loss incurred (Patterson, Cowley, and Prasongsukarn 2006). Complaint recovery refers to the steps companies take to neutralize the potentially drastic effects of the failure and restore the customer to a state of satisfaction (Patterson, Cowley, and Prasongsukarn 2006; Simons and Kraus 2005). A recent comprehensive review of journal articles on complaint recovery suggests nearly 97% of the published articles tested the effectiveness of recovery responses while revealing a total of 21 different potential recovery measures (Van Vaerenbergh et al 2019).…”
Section: Conceptual Framework and Theoretical Backgroundmentioning
confidence: 99%
“…While even the most customer-oriented companies experience service failures, how they react to customer complaints and service failures are somewhat under their control. Previous studies suggest that 9 of the 10 customers who experience a failure would return if their issue was properly resolved; this ratio plunges to 22% if the situation is not handled appropriately (Simons and Kraus 2005). Hence, it is vital that when companies face a failure situation, they identify appropriate recovery strategies that can deliver the desired outcome.…”
mentioning
confidence: 99%
“…Positive correlations between customer satisfactions and repurchase intentions that led to future profitability were verified (Simon and Kraus, 2005). Proper responses to failures enhance customer loyalty (Hart et al, 1990).…”
Section: Service Recoverymentioning
confidence: 92%
“…Simons (2004) [45] questioned the focus of service recovery on dealing with customers who have been the recipient of poor service and suggested that it should focus more on dealing with the mechanisms that generate errors and improve correction capabilities. Learning from failures moves service recovery away from a transactional activity, interested only in recovering and satisfying an individual customer, toward management activity that improves systems and processes to ensure future customers are satisfied and costs are reduced.…”
Section: Thefinancial Aspect Of Service Recoverymentioning
confidence: 98%